Impact of Enforcement on Healthcare Billing Fraud: Evidence from the USA - Flasher, Renee (Journal of business ethics, 2019)
Each state’s Medicaid Fraud Control Unit (MFCU) prosecutes billing fraud cases against individual healthcare providers who fraudulently bill Medicaid for services provided. Once an individual is convicted of billing fraud, the Office of Inspector General for the Department of Health and Human Services may exclude the individual from billing any federal government healthcare program, including Medicaid. Excluded individuals are added to a public list of exclusions, which restricts their ability to practice professionally. Prompted by criminology research into the impact of policing resources, we test whether these government enforcement initiatives against fraud serve as a deterrent to would-be fraudulent billers. We document that key enforcement proxies, the staffing level and budget of an MFCU, are positively associated with the yearly number of exclusions added at the state level. Our results are consistent with the exclusion list not being a deterrent but provide support for MFCUs’ fraud detection efforts. This paper provides industry-specific fraud insights for auditors and other individuals involved in public policy, specifically Medicaid, and introduces a novel dataset to the accounting fraud research literature.